Cerebral cavernous malformations: Prevalence of cardiovascular comorbidities and allergic diseases compared to the normal population. (3rd April 2021) - Dammann, Philipp; Saban, Dino Vitali; Herten, Annika; Chen, Bixia; Zhu, Yuan; Santos, Alejandro; Rauschenbach, Laurèl; Wrede, Karsten; Jabbarli, Ramazan; Schmidt, Börge; Jöckel, Karl‐Heinz; Kleinschnitz, Christoph; et al.
Abstract: Background: To determine the prevalence of cardiovascular comorbidities and allergic diseases in patients with cavernous malformations of the central nervous system compared to the normal population. Methods: Clinical and magnetic resonance imaging data of 1352 patients with cerebral cavernous malformations (CCM) from an observational, cross‐sectional, single‐institutional study were analyzed and compared to an age‐and‐gender stratified and matched sample from a population‐based, epidemiological study assessing cardiovascular risk factors in the local normal population of the same area (RECALL study). Results: Of 1352 patients, 810 (60%) were female. Mean age was 40.4 ± 16 years. 221 patients (16%) suffered from familial disease. Presence of cardiovascular risk factors and intake of certain drugs in the overall cohort was mostly equal to the normal population reference sample ( n  = 786). The prevalence of allergic diseases was found to be significantly higher in all CCM patients compared to the normal population (30% vs. 20%, odds ratio [OR] 1.35 [1.12–1.63]) and in sporadic CCM cases compared to the normal population and familial cases (32% vs. 20% (OR 1.46 [1.19–1.78], p  = 0.0001) and 22% vs. 20%, respectively). Conclusions: We present novel data on CCM using a large single‐institution and population‐based setup. The study elaborates disease characteristics of CCM patients in detail. For the first time, evidence for an unexplained high prevalence of allergic diseases in this patient population is described (differing between sporadic and familial cases), supporting the hypothesis that immune response is involved in the pathogenesis of CCM.